A Generalized Cash Flow Approach to Short-Term Financial Decisions - Sartoris, William L.; Hill, Ned C. (Journal of Finance, 1983)
William L. Sartoris, Ned C. Hill, A Generalized Cash Flow Approach to Short-Term Financial Decisions, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 349-360